Socio-Emotional Skills in Basic Education Principals. Systematic Literature Review - Nava-Lara, Sergio (2022)
Socio-emotional skills are inseparable from the leadership role played by school principals in elementary education, so it becomes necessary to know which of them are highlighted in the recent literature. This article explores the existing literature about elementary school principals, with an emphasis on the socio-emotional skills that stand out in the performance of their role as leaders of the school community. The exploration is based on a systematic review of the literature, which is a method that allows to know a topic in depth. The results show that all the articles refer to some specific socio-emotional ability; most research is based on qualitative methods; the quantitative studies declare limitations in the representativeness of the results. In addition, there is a tendency to recommend the use of mixed methods for further research.